The current state of citizen science as a tool for ecological research and public engagement. Issue 6 (1st August 2012) - Dickinson, Janis L; Shirk, Jennifer; Bonter, David; Bonney, Rick; Crain, Rhiannon L; Martin, Jason; Phillips, Tina; Purcell, Karen
Abstract : Approaches to citizen science – an indispensable means of combining ecological research with environmental education and natural history observation – range from community‐based monitoring to the use of the internet to "crowd‐source" various scientific tasks, from data collection to discovery. With new tools and mechanisms for engaging learners, citizen science pushes the envelope of what ecologists can achieve, both in expanding the potential for spatial ecology research and in supplementing existing, but localized, research programs. The primary impacts of citizen science are seen in biological studies of global climate change, including analyses of phenology, landscape ecology, and macro‐ecology, as well as in sub‐disciplines focused on species (rare and invasive), disease, populations, communities, and ecosystems. Citizen science and the resulting ecological data can be viewed as a public good that is generated through increasingly collaborative tools and resources, while supporting public participation in science and Earth stewardship.